RAZLIKE U MORFOLOŠKIM KARAKTERISTIKAMA IZMEĐU BOKSERA I NESPORTISTA - Izet Kahrović; Benin Murić; Oliver Radenković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This research was conducted with the aim to define differences in morphological characteristics between boxers and non/athletes of the same age. Sample encompassed 120 subjects having 60 students non/athletes and 60 students actively engaged in sports. For the evaluation of morphological characteristics there were conducted 12 measuring instruments. Testing of the posted hypotheses was performed on the basis of statistical data. The obtained results of this research in anthropometric area have shown that there is statistically significant difference between selected boxers and students not going in for box. This difference is defined by significantly better values and results in anthropometric measures that could be influenced in training activities these being /skin fold thickness and scopes, all in favour of selected boxers.